Coaching for Better Teaching: A Study on Student-Centered Instructional Coaching - Serpil TEKIR (Anı Publishing, 2022)
As the appeal and need for greater student achievement have been increasing each day steadily, so does the wish to find ways to reach those levels. The student-centered coaching (SCC) model is designed to improve teachers' instructional abilities that will improve student achievement. This research study aimed to examine the perceived impact of SCC on teachers' instructional practices and the challenges to and facilitating factors in implementation. The study employed a qualitative phenomenological research design to investigate the student-centered coaching practice of a school district in Northern USA. Qualitative data collected from seven teachers and three coaches who were conveniently available to participate in the study through semi-structured interviews were subjected to content analysis. The results suggested that the respondents considered SCC as an effective model to change teacher practice and ultimately impact student learning. Based on the qualitative data, a few recommendations were offered to help address potential challenges in implementing the SCC in the future.